The Relational View: Future challenges for a non-confirmed expectation - Tescari, Fábio Campos; Brito, Luiz Artur Ledur (Review of Business Management, 2018)
Purpose – Despite its theoretical potential, the relational view proposed by Dyer and Singh (1998) has not been established as a dominant theoretical framework, since the concomitant use of its main constructs is rare. This paper intended to test the relational view considering the impact of its constructs on the economic value created in relationships between buyers and suppliers. Design/methodology/approach – A cross-sectional survey with 121 respondents was conducted in the Brazilian chemical sector. To analyze the measurement models and test the hypotheses, confirmatory factor analysis and multiple linear regression were used. Findings – The limited support for the hypotheses tested suggests that the operationalization of the relational view as an explanatory theory requires further study. Asset specificity seems to be the most solid construct, with a relevant effect on the relational value, and it is present in some moderating effects on environmental variables. The results also suggest that relational governance has some effect on the value captured by the supplier. Originality/value – In addition to the need to review the operationalization of the Relational View, the proposed value measurement model contributed to identifying differences between the value created for the buyer and the value created for the supplier. The measurement scales of value creation presented good quality of fit and also represent a contribution for further research.